Perceived Stress, Individual Psychological Resources, and Social Resources Among Computer Science Students During the COVID-19 Pandemic - Höhne, Elisabeth; Fekete, Sándor P.; Schild, Jonas; Zander, Lysann (Frontiers in Education, 2022)
Due to the COVID-19 pandemic, university students worldwide have experienced drastic changes in their academic and social lives, with the rapid shift to online courses and contact restrictions being reported among the major stressors. In the present study, we aimed at examining students’ perceived stress over the course of the pandemic as well as individual psychological and social coping resources within the theoretical framework of the Transactional Model of Stress and Coping in the specific group of STEM students. In four cross-sectional studies with a total of 496 computer science students in Germany, we found that students reported significantly higher levels of perceived stress at both measurement time points in the second pandemic semester (October/November 2020; January/February 2021) as compared to the beginning of the first (April/May 2020), indicating that students rather became sensitized to the constant pandemic-related stress exposure than habituating to “the new normal”. Regarding students’ coping resources in the higher education context, we found that both high (a) academic self-efficacy and (b) academic online self-efficacy as well as low (c) perceived social and academic exclusion among fellow students significantly predicted lower levels of students’ (d) belonging uncertainty to their study program, which, in turn, predicted lower perceived stress at the beginning of the first pandemic semester. At the beginning of the second pandemic semester, we found that belonging uncertainty still significantly mediated the relationship between students’ academic self-efficacy and perceived stress. Students’ academic online self-efficacy, however, no longer predicted their uncertainty about belonging, but instead had a direct buffering effect on their perceived stress. Students’ perceived social and academic exclusion among fellow students only marginally predicted their belonging uncertainty and no longer predicted their perceived stress six months into the pandemic. We discuss the need and importance of assessing and monitoring students’ stress levels as well as faculty interventions to strengthen students’ individual psychological and social coping resources in light of the still ongoing pandemic.